Rancang Bangun Mesin Pengiris Singkong - Fajar Kurnia Putra; Safril Safril; Desmarita Leni; Veny Selviyanty YH (Jurnal Teknik Mesin, 2019)
The design of the cassava slicer machine has a capacity of 38 kg / hour, this machine is designed to design a cassava slicing machine that has high usability, achieving the required motor power so that the desired engine capacity can be achieved, able to determine the exact method of slicing cassava . The working principle of Cassava Slicing Machine is to work when the electric motor is turned on, then the motor will rotate then the motor rotation is transmitted to the pulley, moving the slicing knife by 0.03653 N / mm2. After the shaft rotates, the disc where the blade will rotate and the cassava is ready for slices and the results of the cassava slices will come out through the output funnel. Cassava slicing machine using 1/2 HP motor with 1400 rpm rotation as its driver, and Framework with L St.37 profile material, type A belt, bearing with UCP205-16 type